Vulnerabilidade. Águas subterrâneas. Aquíferos. DRASTIC. Contaminação. - Tanajura, Douglas da Silva (2016)
Groundwater represents approximately 98% of available fresh water suitable for human consumption. Although this is a hard access resource and relative natural protection, there are several human activities with potential to contamination of susceptible aquifers. The vulnerability of groundwater is an intrinsic property of the physical environment and is the ease or difficulty of a hypothetical contaminant to vertically migrate from the ground surface to the aquifer. The objective of this study was apply the DRASTIC method to quantify the groundwater intrinsic vulnerability in unconfined aquifers from Hydrographic Sub-Basin Jacaré-Pepira (component of the UGHRI-13). For the Standard DRASTIC method was found vulnerability 48.96% Moderate, 44.14% and 6.90% Low High (not occurring Vulnerability Very High). For DRASTIC Pesticides, was found vulnerability 53.54% Moderate, 37.27% High 4.72% Very High and Low 4.47%. Considering the costs and time required for aquifers remediation, it’s proposed the use of intrinsic vulnerability mapping of the physical environment on preliminary evaluations against the installation of new enterprises.